Impact of periprocedural atrial fibrillation on short-term clinical outcomes following percutaneous coronary intervention - Chan, W.; Ajani, A.; Clark, D.; Stub, D.; Andrianopoulos, N.; Brennan, A.; New, G.; Sebastian, M.; Johnston, R.; Walton, A.; Reid, Christopher; Dart, A.; et al. (2012)
There are few data on the incidence and clinical outcomes of patients with atrial fibrillation (AF) treated in the era of percutaneous coronary intervention (PCI). We analyzed 30-day clinical outcomes in 3,307 consecutive patients with and without AF (sinus rhythm) undergoing PCI from January 2007 through December 2008 enrolled in a multicenter Australian registry. Periprocedural AF was present in 162 patients (4.9%). AF was associated with older age (74.1 ± 8.9 vs 63.9 ± 11.9 years, p <0.001), higher baseline serum creatinine (0.13 ± 0.14 vs 0.10 ± 0.13 mmol/L, p = 0.01), and lower left ventricular ejection fraction (49.5 ± 13.2% vs 53.4% ± 11.6%, p <0.001). Significantly more patients with AF had a history of heart failure and cerebrovascular and peripheral arterial diseases (p =0.01 for all comparisons). Periprocedural glycoprotein IIb/IIIa inhibitor (31.5% vs 31.4%, p = 0.98) and antithrombin use were not different between groups, but in-hospital bleeding complications were higher in patients with AF (5.0% vs 2.1%, p = 0.015). Fewer patients with AF received drug-eluting stents (p = 0.004). AF was associated with a greater than fourfold increase in 30-day mortality (9.9% vs 2.2%, p <0.0001) and readmission rates at 30 days (p = 0.01). Fewer patients with AF were on dual antiplatelet therapy at 30 days (86.3% vs 94.3%, p <0.0001), although 28.1% of patients with AF were on triple therapy (dual antiplatelet therapy plus oral anticoagulation). In conclusion, patients with periprocedural AF represent a very high-risk group. Excess 30-day morbidity and mortality after PCI may be due to the higher incidence of co-morbidities, bleeding complications, and suboptimal antiplatelet therapy. © 2012 Elsevier Inc. All rights reserved.